Ancestors of the Minoan sword: Early Minoan IB long daggers from Hagia Photia, Crete - Costis Davaras; Philip P. Betancourt; Alessandra Giumlia-Mair; Susan C. Ferrence (UISPP Journal)
The long sword, a weapon first known in the Aegean Bronze Age from Middle Minoan Crete (early second millennium BC), represented the culmination of a long period of development. Several problems in both casting and forging had to be solved before the production of large implements like swords could be achieved. Very early experiments with long weapons come from Early Minoan IB Crete, early in the third millennium BC. Examples from the cemetery at Hagia Photia illustrate this early phase in the production of large implements.